Public policy for productive and healthy workplaces. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – The paper aims to discuss different ways in which public policymakers can intervene to support workplace innovation. Government intervention and regulation in the economy and labour market are much too important to be treated as an ideological battleground. Despite the availability of evidence that workplace innovation can improve organisational performance and employee well-being, too few companies and public sector bodies are acting on it. This has implications for a wide range of economic and social policy goals, not least at a time when Europe struggles to emerge from recession. Design/methodology/approach: – The paper calls for a mature and informed debate about "what works", not least regarding the ways in which public policy can help to close the gap and generate win-win outcomes for enterprises and their employees. Findings: – It looks at the different ways in which public policymakers can intervene to support workplace innovation and provides evidence from a number of countries which points to the benefits of a multidimensional approach based on policies which lead to close collaboration and shared understanding between employers' organisations, trade unions, business support organisations, chambers of commerce and universities. Originality/value: – Drawing on evidence from Finland, Flanders, France, Germany and Norway, it shows that there is an urgent need for new thinking about how public policy can help to shape more productive and healthier workplaces in much of Europe and that public intervention should be redefined in a way that reflects the evidence of what actually works in practice.